2000
DOI: 10.1007/s004649900005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted distal gastrectomy for early gastric cancer

Abstract: Although LG requires longer surgical time, this retrospective study suggests that it is superior to open surgery in terms of faster postoperative recoveries, shorter hospital stays, and cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 25 publications
2
73
0
2
Order By: Relevance
“…Many studies have shown the advantages of LADG over open distal subtotal gastrectomy (ODSG), such as cosmetic benefits, less pain, faster recovery, and shorter hospital stay [2][3][4][5][6][7]. The early postoperative quality of life (QoL) following LADG has been shown to be superior to that following ODSG [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the advantages of LADG over open distal subtotal gastrectomy (ODSG), such as cosmetic benefits, less pain, faster recovery, and shorter hospital stay [2][3][4][5][6][7]. The early postoperative quality of life (QoL) following LADG has been shown to be superior to that following ODSG [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in 1991 [9], laparoscopy-assisted gastrectomy (LAG) has gained widespread, international acceptance among surgeons as one of the best treatments for early gastric cancer (EGC) [18]. LAG provides many other advantages when compared with conventional open gastrectomy: less blood loss and inflammation, better post-operative pulmonary function, less postoperative pain, earlier first flatus and eating, shorter hospital stays, and better cosmesis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of early gastric cancer in Korea has been increasing because of recent improvements in early diagnosis [3]. Many studies have focused on improving the quality of life and achieving an early recovery after operation by performing minimally invasive surgery instead of open surgery for treating early gastric cancer [4][5][6][7]. Gastric surgeons have displayed great interest in laparoscopic surgery for early gastric cancer because laparoscopic surgery has many advantages over conventional open surgery in terms of the patients' quality of life [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on improving the quality of life and achieving an early recovery after operation by performing minimally invasive surgery instead of open surgery for treating early gastric cancer [4][5][6][7]. Gastric surgeons have displayed great interest in laparoscopic surgery for early gastric cancer because laparoscopic surgery has many advantages over conventional open surgery in terms of the patients' quality of life [4][5][6][7]. We have reported a comparative study of laparoscopic surgery and conventional open surgery for gastric cancer [7], and a number of authors have recently presented their experiences with laparoscopic surgery for the treatment of early gastric cancer [4,7,8].…”
Section: Introductionmentioning
confidence: 99%